The water cure - Mackintosh, Sophie (Hamish Hamilton, 2018)
"You are a girl. Your body is vulnerable. Men will break it if they can - and out there, they absolutely will. Bodies must be controlled in order to be safe. Suffering will prepare you for the worst - the cure is nothing compared to what you've been spared in the sickness. It takes a lot of love to hurt you like this. Now come outside. It's time to play the drowning game." -- Back cover.